Dynamically Cross-Linked Self-Assembled Thermoresponsive Microgels with Homogeneous Internal Structures - Mueller, Eva (Langmuir : the ACS journal of surfaces and colloids, 2018)
The internal morphology of temperature-responsive degradable poly(N-isopropylacrylamide) (PNIPAM) microgels formed via an aqueous self-assembly process based on hydrazide and aldehyde-functionalized PNIPAM oligomers is investigated. A combination of surface force measurements, small angle neutron scattering (SANS), and ultrasmall angle neutron scattering (USANS) was used to demonstrate that the self-assembled microgels have a homogeneously cross-linked internal structure. This result is surprising given the sequential addition process used to fabricate the microgels, which was expected to result in a densely cross-linked shell-diffuse core structure. The homogeneous internal structure identified is also significantly different than conventional microgels prepared via precipitation polymerization, which typically exhibit a diffuse shell-dense core structure. The homogeneous structure is hypothesized to result from the dynamic nature of the hydrazone cross-linking chemistry used to couple with the assembly conditions chosen that promote polymer interdiffusion. The lack of an internal cross-linking gradient within these degradable and monodisperse microgels is expected to facilitate more consistent drug release over time, improved optical properties, and other potential application benefits